The Analysis of the Fiqh (Islamic Jurisprudence) Works ff Abu Barakat - Akhmedov Sayqal Abdurahmonovich (Periodica Journal, 2022)
The great Hanafi scholar Abu al-Barakat al-Nasafi, who lived and worked in the twelfth and thirteenth centuries, made a great contribution to the development of Hanafi jurisprudence with his works in jurisprudence. In particular, the work "Al-Kanz", which is a commentary work to "Al-Wafi" by scholar, is one of the latest works on the sect and to this day it serves as a major guide for the students
Keywords: fiqh; Al-Wafi; Hadith; tafsir